2021
DOI: 10.21608/edj.2021.71338.1575
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between bond strength of lithium disilicate with preheated composite, flowable composite and resin cement

Abstract: Objective: investigation of the microshear bond strength between lithium disilicate with preheated viscous composite, flowable composite and resin cement by comparison of their microshear bond strength.Material and method: forty-five samples were prepared and divided into three groups; preheated viscous composite, flowable composite and resin cement. Materials were injected into plastic transparent molds (2 mm height, 2 mm diameter) on the surface of lithium disilicate discs previously surface treated with cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…25 Two studies analyzing bond strength to lithium disilicate reported similar values when preheated CR, resin cement and flowable CR were compared. 30,51 Seven out of nine studies showed high conversion degree after preheating the CR, 13,15,28,34,[46][47][48] but two studies showed that preheating did not increase the conversion degree. 23,34 In most studies, increased temperature also increased microhardness of CR.…”
Section: Summary Of Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…25 Two studies analyzing bond strength to lithium disilicate reported similar values when preheated CR, resin cement and flowable CR were compared. 30,51 Seven out of nine studies showed high conversion degree after preheating the CR, 13,15,28,34,[46][47][48] but two studies showed that preheating did not increase the conversion degree. 23,34 In most studies, increased temperature also increased microhardness of CR.…”
Section: Summary Of Resultsmentioning
confidence: 98%
“…Of six studies that assessed bond strength using preheated CR, four analyzed bonding to dentin, 22,25,38,50 and two the bonding to lithium disilicate ceramics 30,51 . In two studies, preheated CR showed higher bond strength to dentin than unheated CR, 38,50 only one study did not report significant differences 22 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations